Penerapan STEAM Berbantuan E-Modul Berbentuk Interactive Magazine untuk Meningkatkan Literasi Matematis Siswa SMP - Nainggolan, Iska Barbara; Simatupang, Gugun Manosor; Theis, Roseli; Novferma, Novferma (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2025)
Mathematical literacy plays a crucial role, as many daily human activities are related to mathematics and require literacy skills to solve real-life problems. However, students' mathematical literacy in Indonesia remains relatively low, as shown by international assessments and classroom observations. One effective approach to improve mathematical literacy is STEAM-based learning (Science, Technology, Engineering, Art, and Mathematics), which emphasizes interdisciplinary collaboration in solving real-world problems. This study aims to enhance junior high school students’ mathematical literacy through the implementation of STEAM-based learning supported by an interactive magazine e-module. The research employed an experimental method with a one-group pretest-posttest design. Data were analyzed using normality testing and non-parametric hypothesis testing to examine students’ learning progress, along with gain analysis to measure the level of improvement. The results show that students’ mathematical literacy improved after the implementation of the learning approach. These findings support that STEAM-based learning assisted by an interactive e-module can serve as an effective alternative to enhance students’ understanding and application of mathematical concepts in real-life contexts